Face-to-face physiotherapy compared with a supported home exercise programme for the management of musculoskeletal conditions: protocol of a multicentre, randomised controlled trial—the REFORM trial - David Wong; Catherine Sherrington; Manuela L Ferreira; Christopher G Maher; Lisa A Harvey; Hannah G Withers; Joanne V Glinsky; Jackie Chu; Matthew D Jennings; Alison J Hayes; Ian J Starkey; Blake A Palmer; et al. (BMJ Open, 2021)
Introduction Exercise, support and advice are considered core components of management for most musculoskeletal conditions and are typically provided by physiotherapists through regular face-to-face treatments. However, exercise can be provided remotely as part of a home exercise programme, while support and advice can be provided over the telephone. There is initial evidence from trials and systematic reviews to suggest that remotely provided physiotherapy can be used to manage a variety of musculoskeletal conditions safely and effectively.Methods and analysis The aim of this single-blind randomised controlled non-inferiority trial is to determine whether a supported home exercise programme is as good as or better than face-to-face physiotherapy for the treatment of musculoskeletal conditions. Two hundred and ten participants will be recruited from five public hospitals in Sydney, Australia. Participants will be randomised to either the supported home exercise group or the face-to-face physiotherapy group. Participants allocated to the supported home exercise group will initially receive one face-to-face session with the trial physiotherapist and will then be managed remotely for the next 6 weeks. Participants allocated to the face-to-face physiotherapy group will receive a course of physiotherapy as typically provided in Sydney government hospitals. The primary outcome is function measured by the Patient Specific Functional Scale at 6 weeks. There will be nine secondary outcomes measured at 6 and 26 weeks. Separate analyses will be conducted on each outcome, and all analyses will be conducted on an intention-to-treat basis. A health economic evaluation will be conducted from a health funder plus patient perspective.Ethics and dissemination Ethical approval was obtained on the 17 March 2017 from the Northern Sydney Local Health District HREC, trial number HREC/16HAWKE/431-RESP/16/287. The results of this study will be submitted for publication to peer-reviewed journals and be presented at national and international conferences. Recruitment commenced in March 2019, and it is anticipated that the trial will be completed by December 2021. This trial will investigate two different models of physiotherapy care for people with musculoskeletal conditions.Trial registration number CPMP/ICH-135/95.Protocol version The most recent version of the protocol is V.1.2 dated November 2019.